Needlework and John Ruskin’s “acicular art of nations” - Rachel M. W. DICKINSON (E-REA)
This essay outlines Victorian cultural critic John Ruskin’s use of needlework. Paying particular attention to textiles in the opening and closing of Fors Clavigera (1871-1885), and highlighting educational texts by two women cited there (Kate Stanley and Millicent Garrett Fawcett), this paper argues that Ruskin blurs the boundaries of Victorian Britain’s hierarchical classifications of gender, class, nation and art. Mapping a shift in Ruskin’s knowledge and use of needlework, particularly as negotiated through learning about plain sewing and embroidery from Stanley, it demonstrates how Ruskin takes a traditionally feminine form of work and uses it to teach universal lessons.